1998
DOI: 10.1046/j.1365-2265.1998.00418.x
|View full text |Cite
|
Sign up to set email alerts
|

The low dose ACTH test in chronic fatigue syndrome and in health

Abstract: This study provides further evidence for a subtle pituitary-adrenal insufficiency in subjects with chronic fatigue syndrome compared to healthy volunteers. Disparities between our healthy volunteer data and those of other groups using the 1 microgram ACTH test suggest that the test may not be as reliable as previously indicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
1
4

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(38 citation statements)
references
References 35 publications
(49 reference statements)
2
31
1
4
Order By: Relevance
“…Scott and colleagues [16] also reported reduced ACTH responses to CRH challenge, but noted reduced cortisol responses, whereas Cleare and colleagues [17] reported normal ACTH responses but attenuated cortisol responses. Tests utilizing ACTH administration demonstrate equally unclear results [15,18,19]. In light of this study, it is possible that genetic variations in POMC and NR3C1 may contribute to the pathophysiology of a subgroup of patients with chronic fatigue, and this heterogeneity may explain the previous inconsistencies in the literature.…”
Section: Discussionmentioning
confidence: 74%
“…Scott and colleagues [16] also reported reduced ACTH responses to CRH challenge, but noted reduced cortisol responses, whereas Cleare and colleagues [17] reported normal ACTH responses but attenuated cortisol responses. Tests utilizing ACTH administration demonstrate equally unclear results [15,18,19]. In light of this study, it is possible that genetic variations in POMC and NR3C1 may contribute to the pathophysiology of a subgroup of patients with chronic fatigue, and this heterogeneity may explain the previous inconsistencies in the literature.…”
Section: Discussionmentioning
confidence: 74%
“…However, other studies found no difference in salivary cortisol concentrations between CFS and healthy controls [91,92]. Insight from pharmacological challenge studies testing specific levels of HPA axis regulation indicates enhanced feedback sensitivity [92][93][94][95], increased adrenocortical sensitivity to adrenocorticotropic hormone (ACTH), and a reduced maximal cortisol response compared to normal subjects [81,96], with nonsignificant findings being reported also [97,98]. Clearly, findings point toward relative hypocortisolism in CFS.…”
Section: Findings On Hpa Axis and Cfsmentioning
confidence: 84%
“…[6][7][8][9][10] This downregulation of the hypothalamicpituitary-adrenal (HPA) axis in CFS stands in contrast to the upregulation seen in major depression. Serotonergic and noradrenergic hypothalamic pathways, [11][12][13] and growth hormone secretion 14 also are disrupted.…”
Section: Neuroendocrine Studiesmentioning
confidence: 88%